A win-win scenario for photosynthesis and the plasma membrane H+ pump - Kinoshita, Satoru N.; Kinoshita, Toshinori (Frontiers in Plant Science, 2022)
In plants, cytosolic and extracellular pH homeostasis are crucial for various physiological processes, including the uptake of macronutrients and micronutrients, cell elongation, cell expansion, and enzyme activity. Proton (H+) gradients and the membrane potential are generated by a H+ pump consisting of an active primary transporter. Plasma membrane (PM) H+-ATPase, a PM-localized H+ pump, plays a pivotal role in maintaining pH homeostasis in plant cells and extracellular regions. PM H+-ATPase activity is regulated by protein abundance and by post-translational modifications. Several stimuli have been found to activate the PM H+-ATPase through phosphorylation of the penultimate threonine (Thr) of the carboxy terminus. Light- and photosynthesis-induced phosphorylation of PM H+-ATPase are conserved phenomena among various plant species. In this work, we review recent findings related to PM H+-ATPase regulation in the photosynthetic tissues of plants, focusing on its mechanisms and physiological roles. The physiological roles of photosynthesis-dependent PM H+-ATPase activation are discussed in the context of nitrate uptake and cytoplasmic streaming in leaves.